Tratamiento quirúrgico de los aneurismas de la aorta abdominal: Round table XXVI Uruguayan Congress of Surgery: coordinator Rómulo Danza - Danza, Rómulo; Arias, José; Gateño, Nisso; Goller, Wofgang; Matteucci, Pablo; Mazza, Milton; Palma, Eduardo; Ugarte, Raúl (Cirugía del Uruguay, 1976)
t is for me a great honor and one. high responsibility to coordinate the Redo Table: round about Abdominal Aortic Aneurysm Surgery at the XXVI Uruguayan Congress of Surgery. On behalf of the Uruguayan Angiology Society and on my own behalf I extend our gratitude to the Executive Committee of the Congress for inviting us to organize this Roundtable •. The Society of Angiology is present for the second time at this great scientific event and hopes to contribute with this exchange of experience, so necessary, between the different branches of the surgical discipline, to provide a wealth of current knowledge useful to the surgeon, general · and the specialized surgeon.